Exposure to bacteriophages t4 and m13 increases integrin gene expression and impairs migration of human pc-3 prostate cancer cells - Sanmukh, Swapnil Ganesh [UNESP]; Santos, Nilton J. [UNESP]; Barquilha, Caroline Nascimento [UNESP]; Dos Santos, Sérgio Alexandre Alcantara [UNESP]; Duran, Bruno Oliveira Silva; Delella, Flávia Karina [UNESP]; Moroz, Andrei [UNESP]; Justulin, Luis Antonio [UNESP]; Carvalho, Hernandes F.; Felisbino, Sérgio Luis [UNESP] (MDPI, 2021)
The interaction between bacteriophages and integrins has been reported in different cancer cell lines, and efforts have been undertaken to understand these interactions in tumor cells along with their possible role in gene alterations, with the aim to develop new cancer therapies. Here, we report that the non-specific interaction of T4 and M13 bacteriophages with human PC-3 cells results in differential migration and varied expression of different integrins. PC-3 tumor cells (at 70% confluence) were exposed to 1 × 107 pfu/mL of either lytic T4 bacteriophage or filamentous M13 bacteriophage. After 24 h of exposure, cells were processed for a histochemical analysis, wound-healing migration assay, and gene expression profile using quantitative real-time PCR (qPCR). qPCR was performed to analyze the expression profiles of integrins ITGAV, ITGA5, ITGB1, ITGB3, and ITGB5. Our findings revealed that PC-3 cells interacted with T4 and M13 bacteriophages, with significant upregulation of ITGAV, ITGA5, ITGB3, ITGB5 genes after phage exposure. PC-3 cells also exhibited reduced migration activity when exposed to either T4 or M13 phages. These results suggest that wildtype bacteriophages interact non-specifically with PC-3 cells, thereby modulating the expression of integrin genes and affecting cell migration. Therefore, bacteriophages have future potential applications in anticancer therapies.
Keywords: Bacteriophage; Cell migration; Integrin; Nanoparticle; PC-3; Prostate cancer